The Effect of IFRS 16 Adoption on Earnings Quality and Audit Fees: Evidence From the Airline Industry - Li, Chunyu (2022)
This research focuses on the International Financial Reporting Standard (IFRS) 16 Lease adoption’s impact on the airline industry, especially from the perspectives of earnings quality and audit fees, which represents to evaluate the effect from the benefits consequences and costs consequence view respectively. This research aims to discover the relations between the adoption of IFRS 16 and earnings quality and audit fees. So, this aim determines that the accruals regression model from Dechow and Dichev (2002) and audit fees change regression model underlies by the De George et al. (2013) will be utilized to have the empirical study by sampling the major airlines around the world. Based on the empirical research by these regression models and the airline industry characteristics, this paper derives that the IFRS 16 adoption has a positive impact on the airlines’ earnings quality and audit fees.